2017
DOI: 10.3390/molecules22081274
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, Leptin, and Leptin Receptor in Obese Patients with Type 2 Diabetes Treated with Insulin Detemir

Abstract: The aim of the present study is to quantitatively assess the expression of selected regulatory molecules, such as leptin, leptin receptor, and adiponectin in the blood of obese patients with type 2 diabetes both before treatment and after six months of pharmacological therapy with the long-lasting insulin analogue, insulin detemir. A significant decrease in the analysed regulatory molecules, i.e., leptin receptor and adiponectin, was found in blood plasma of the patients with untreated type 2 diabetes. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Additionally, mutual regulation occurs between leptin, adiponectin, and insulin. Leptin inhibits the secretion of insulin in peripheral tissues, whereas adiponectin improves insulin sensitivity . The expression levels of leptin and adiponectin measured using ELISA were significantly reduced in the T2DM group.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, mutual regulation occurs between leptin, adiponectin, and insulin. Leptin inhibits the secretion of insulin in peripheral tissues, whereas adiponectin improves insulin sensitivity . The expression levels of leptin and adiponectin measured using ELISA were significantly reduced in the T2DM group.…”
Section: Discussionmentioning
confidence: 91%
“…The results indicated increased serum leptin levels with longer diabetes duration, which also correlated positively with leptin resistance, and this might be relevant for the pathogenesis/progression of T2D. Leptin levels have been previously shown to be higher in T2D patients than healthy controls and to be predictors for the risk of developing diabetes . A strong inverse correlation between serum leptin and sObR concentrations was also noted, possibly indicative of a reciprocal interaction: hyperleptinemia may down‐regulate sObR, while sObR may change leptin clearance and half‐life .…”
Section: Discussionmentioning
confidence: 74%
“…Leptin levels have been previously shown to be higher in T2D patients than healthy controls and to be predictors for the risk of developing diabetes. 25,26 A strong inverse correlation between serum leptin and sObR concentrations was also noted, possibly indicative of a reciprocal interaction: hyperleptinemia may down-regulate sObR, while sObR may change leptin clearance and half-life. [27][28][29] Moreover, gender-specific differences in leptin/leptin-receptor system were observed, as females had higher leptin and lower sObR concentrations, and were more leptin resistant/less leptin sensitive.…”
Section: Discussionmentioning
confidence: 91%
“…Leptin is a hormone produced primarily in the adipocytes of the white adipose tissue [3] and is the key biomarker of the adipose tissue [4], which is closely related to obesity, diabetes, and metabolic syndrome [5][6][7][8]. e study found that elevated serum leptin levels contribute to the development of metabolic complications of obesity, especially diabetes and insulin resistance [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%